Kleinsculptuur. (Antwerpen : Gemeentekrediet van België)
Algoet, Erik ; Arnould, Marcel ; Bailleux, Cesar ; Bal, Eduard ; Caille, Pierre ; Canestrard, Livia ; Cardon, Eric ; Courtois, Albin ; De Clercq, Maurice ; De Leeuw, Bert ; De Maeyer, Jacky ; De Smet, Etienne ; Depuydt, Etienne ; Eyberg, Adré ; Dionyse, Carmen ; Dries, Jan ; Gabriel, Henri ; etc.
Kleinsculptuur, Gemeentekrediet van België, Antwerpen, s.a.
boek